ICT and learning skill (Journal of Parents and Teachers, 2014)
Learning skill is not innate nor spontaneous but essential in this society of information where, more than ever, what Brooks Adams said becomes real: “they know enough who know how to learn”. Form quotes like Adam’s one, the author reflects about this skill development since the early childhood and summarizes in a chart some resources and applications which are on the Internet and that are useful for this goal.
Keywords: ICT; learning skill; integrated curriculum; resources